2020
DOI: 10.1016/j.ijid.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Community quarantine strategy against coronavirus disease 2019 in Anhui: An evaluation based on trauma center patients

Abstract: The objective of our study was to introduce community quarantine strategy against coronavirus disease 2019 (COVID-19) in Anhui and evaluate the effectiveness of community quarantine based on trauma center (TC) patients. Method: The structure of community quarantine strategy was illustrated. Distribution of injuries among patients in two TCs between January 24, 2020 and February 24, 2020 was described. Multiple linear regression was used to analyze the correlation between the distribution of Injuries in TCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 15 publications
2
34
2
2
Order By: Relevance
“…School closures have also increased the number of children with more unstructured time at home. However, our analysis did not reveal any difference in the number of school-aged children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years old) presenting with traumatic injuries to the ED as a consequence of SAH.…”
Section: A C C E P T E Dcontrasting
confidence: 63%
See 1 more Smart Citation
“…School closures have also increased the number of children with more unstructured time at home. However, our analysis did not reveal any difference in the number of school-aged children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years old) presenting with traumatic injuries to the ED as a consequence of SAH.…”
Section: A C C E P T E Dcontrasting
confidence: 63%
“…In a retrospective analysis of all trauma patients seen at 2 regional trauma centers, the authors noted a slight but insignificant decrease in injuries occurring outdoors, while the number of injuries occurring at home remained unchanged. 7 Another study from the same region examines changes to the mechanism of traumatic injuries. Comparing data from a 4-week period during the height of the pandemic to the same period over the past 5 years, authors note a significant decrease in traumatic traffic injuries and falls.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…8 In Ainhui, China, there was a significant decrease in traffic and outdoor injuries during early stages of community lockdown, and multiple linear regression analysis demonstrated significant correlation between the number of COVID-19 cases and traffic and outdoor injuries. 9 In Barcelona, Spain, Hunez et al reported approximately one-fourth the number of usual emergency trauma visits in the first 20 days of Spain's State of Emergency. 10 Kamine et al also reported a 57.4% decrease in trauma admissions, with an 80.5% decrease in motor vehicle collisions during the lockdown period February-April 2020 in Portsmouth, USA.…”
Section: Discussionmentioning
confidence: 99%
“…While several hospitals found a decreasing trend in general trauma admissions from February to April 2020, none of these studies thoroughly evaluated the effects on emergent operative cases or changes in mechanisms of injury. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18…”
Section: Discussionmentioning
confidence: 99%